2013
DOI: 10.1007/s00439-013-1306-3
|View full text |Cite
|
Sign up to set email alerts
|

BET1L and TNRC6B associate with uterine fibroid risk among European Americans

Abstract: Uterine fibroid (UFs) affect 77% of women by menopause and account for $9.4 billion in healthcare costs each year. Although UFs are heritable, genetic risk is poorly understood. The first genome-wide association study (GWAS) of UFs was recently performed in a Japanese population, with reported genome-wide significance for single nucleotide polymorphisms (SNPs) across three chromosomal regions. We tested these SNPs for association with UFs in U.S. cohorts. Women were enrolled in the Right from the Start (RFTS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 65 publications
5
37
0
Order By: Relevance
“…genome-wide association studies investigating variants associated with the formation of uterine fibroids identified a single-nucleotide polymorphism in the 3 0untranslated region of the BET1L gene directly associated with a decreased risk for developing uterine fibroids in women of European American descent. 24,25 FAM228B, a black-specific PFS candidate associated with better PFS, is a theoretical protein-coding gene encoded on chromosome 2p23.3 that is otherwise largely of unknown function. Furthermore, LIG3, observed as being associated with poor PFS for black patients but improved PFS for white patients, regulates a highly error-prone subtype of alternative nonhomologous end joining DNA repair, termed microhomology-mediated end joining, that can result in an elevated risk of genome instability and increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…genome-wide association studies investigating variants associated with the formation of uterine fibroids identified a single-nucleotide polymorphism in the 3 0untranslated region of the BET1L gene directly associated with a decreased risk for developing uterine fibroids in women of European American descent. 24,25 FAM228B, a black-specific PFS candidate associated with better PFS, is a theoretical protein-coding gene encoded on chromosome 2p23.3 that is otherwise largely of unknown function. Furthermore, LIG3, observed as being associated with poor PFS for black patients but improved PFS for white patients, regulates a highly error-prone subtype of alternative nonhomologous end joining DNA repair, termed microhomology-mediated end joining, that can result in an elevated risk of genome instability and increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genome-wide linkage scan in the affected sister study (ASP) (8) and fine association mapping across the FH -linked region in the NIEHS cohort (16) suggested the presence of a candidate 1q43 gene affecting the risk and size of UL. More recently, epidemiologic studies of UL in American women enrolled in the Right from the Start (RFTS) cohort and the BioVU DNA repository replicated the results of GWAS in a Japanese population for two of the three most significantly associated genes encoding BET1L (blocked early in transport 1 homolog) and TNRC6B (trinucleotide repeat containing 6B) (17, 18). …”
Section: Introductionmentioning
confidence: 90%
“…A subsequent GWAS in women of European descent found that SNPs in the FASN gene were associated with UL, but did not replicate the Japanese GWAS findings [188], nor did the BWHS among African Americans [189]. However, the BioVU and Right From the Start cohorts replicated two SNP associations from the Japanese GWAS among European Americans (blocked early in transport 1 homolog (BET1L) rs2280543, and trinucleotide repeat containing 6B (TNRC6B) rs12484776) [190, 191]. In the BWHS, admixture mapping analyses showed suggestive evidence of association at chromosomes 2, 4, and 10 (2q37, 4p16.1, and 10q26) [189], with the region in chromosome 2 being replicated in the UFS [192].…”
Section: Etiologic Hypotheses and Risk Factorsmentioning
confidence: 99%